Ma: The Realm of Mystery in Sugiura Kohei's 'Asian Grammar of Design' - Nguyen, Hung Ky (The Design Society, 2011)
Since returning from a teaching trip in West Germany in 1967, and from an exploration across the Southern part of Asia, designer Sugiura Kohei has advocated an ‘Asian grammar of design’ as a new model for his graphic design work. It is notable that Sugiura has widely employed ma, a Japanese concept of spiritual aesthetics, as the backbone of his Asian grammar of design. To find out more about his aesthetics, I conducted an interview with him in his Tokyo office on 22nd October 2008. This paper discusses how Sugiura perceives ma, and how it is applied to ‘Tradition et Nouvelles Techniques’ (1984), one of his remarkable poster designs. This paper sheds light on what Sugiura identified as the ‘Realm of mystery’ in his work, and how it informs his creativity.